A Legal Analysis of Digital-Based Fraud Crimes in Indonesia: Analisis Yuridis Terhadap Tindak Pidana Penipuan Berbasis Digital di Indonesia - Yoga Dwi Utama; Muhammad Zainuddin; Idul Hamzah Alid (CV Edujavare Publishing, 2026)
The rapid advancement of digital technology has created new avenues for fraudulent conduct that far exceeds the reach of conventional criminal law. Digital-based fraud encompassing phishing, social engineering, online shopping scams, and fraudulent investment schemes disguised as digital platforms shows a consistently rising trend and inflicts enormous financial losses on Indonesian society. This study examines how Indonesian criminal law constructs liability for digital fraud, particularly through the Criminal Code (KUHP), Law Number 11 of 2008 as amended by Law Number 19 of 2016 on Electronic Information and Transactions (UU ITE), and Law Number 8 of 1999 on Consumer Protection. A normative juridical method is employed, using statutory and conceptual approaches. The analysis reveals that conventional fraud provisions in the Criminal Code are insufficient to capture the unique characteristics of digital fraud, while UU ITE offers more relevant penal provisions yet leaves interpretive uncertainties regarding key elements of the offense. Key challenges identified include difficulties in proving elements of deception and criminal intent in digital contexts, perpetrator anonymity, and insufficient inter-agency coordination in handling cross-border cases. The study recommends strengthened digital investigative capacity, uniform juridical interpretation of digital fraud offense elements, and enhanced technical implementation regulations.